STUDI TENTANG KINERJA SEKTOR PERTANIAN PROVINSI JAMBI TAHUN 2005 - 2009 - Erfit, Erfit (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2014)
This study aims to look at the performance of the agricultural sector of Jambi province during the period 2005 to 2009. The study was conducted using secondary data obtained from various sources. Data were analyzed qualitative and quantitative descriptive descriptively using frequency tables and cross tabulations. Seen from a variety of indicators show the performance of the agricultural sector has been pretty good. From the existing data Jambi provincial agricultural sector has experienced an average growth of 6.56 percent per year and more than half the labor force works in agriculture. However, the achievement of several different indicators, it appeared that the development of agricultural development have not been able to improve the welfare of farmers, this can be seen from the magnitude of the exchange rate of the farmers (NTP), which since 2007 tend to decrease and in 2009 NTP Jambi province less than 100 is 94 , 82. In order to encourage agricultural development in the province of Jambi government has carried out various policies. Given the potential and role of agricultural sector on the economy of the province of Jambi, the agricultural development should be continued and the level will be the future of agribusiness approach. Keywords: Agricultural development, institutional and agribusiness ———————————————————— 1). Staf pengajar Fakultas Ekonomi Unja